A simple-looking relative of the Novikov, Hirota-Satsuma and Sawada-Kotera equations. Issue 4 (2nd October 2019) - Rasin, Alexander G.; Schiff, Jeremy
Abstract : We study the simple-looking scalar integrable equation fxxt 3( fx ft 1) = 0, which is related (in different ways) to the Novikov, Hirota-Satsuma and Sawada-Kotera equations. For this equation we present a Lax pair, a Bäcklund transformation, soliton and merging soliton solutions (some exhibiting instabilities), two infinite hierarchies of conservation laws, an infinite hierarchy of continuous symmetries, a Painlevé series, a scaling reduction to a third order ODE and its Painlevé series, and the Hirota form (giving further multisoliton solutions).